2021
DOI: 10.1007/s00404-020-05943-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the appearance of the cutaneous scar after cesarean section reflect the residual myometrial thickness?

Abstract: Purpose The aim of this study is to utilize the Manchester scar scale (MSS) and ultrasound in investigating the association between uterine wall defects and cutaneous scar characteristics after cesarean section (CS). Methods This is a prospective cohort study. The degree of myometrial loss was quantified by calculating a residual myometrial thickness (RMT) ratio as a percentage of RMT to the pre-cesarean anterior uterine wall thickness. Cutaneous scar asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…6,7 Despite their widespread use, the literature presents a gap in comparative analysis and systematic evaluation of CAU and TVU's efficacy in assessing wound healing post-C-section in twin pregnancies. 8 This meta-analysis aims to fill this gap by systematically reviewing and analysing studies that compare the effectiveness of these two ultrasonography techniques in detecting wound healing stages and identifying potential complications early in the postoperative period. 8,9 This research is significant, as it addresses a critical aspect of post-C-section care in a high-risk group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Despite their widespread use, the literature presents a gap in comparative analysis and systematic evaluation of CAU and TVU's efficacy in assessing wound healing post-C-section in twin pregnancies. 8 This meta-analysis aims to fill this gap by systematically reviewing and analysing studies that compare the effectiveness of these two ultrasonography techniques in detecting wound healing stages and identifying potential complications early in the postoperative period. 8,9 This research is significant, as it addresses a critical aspect of post-C-section care in a high-risk group.…”
Section: Introductionmentioning
confidence: 99%
“…8 This meta-analysis aims to fill this gap by systematically reviewing and analysing studies that compare the effectiveness of these two ultrasonography techniques in detecting wound healing stages and identifying potential complications early in the postoperative period. 8,9 This research is significant, as it addresses a critical aspect of post-C-section care in a high-risk group. By delineating the relative strengths and limitations of CAU and TVU in monitoring wound healing, the study seeks to inform best practices and enhance postoperative management strategies for women undergoing caesarean deliveries in twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4,5) Several studies have shown an association 1 Faculty of Medicine, "Ovidius" University, Constanta, Romania 2 Constanta County Emergency Hospital, Constanta, Romania between these uterine parietal defects and gynecological symptoms in women who have had at least one cesarean delivery, symptoms that include either intermenstrual spotting, chronic pelvic pain, or their association. (6,7) This study aims to show whether anemia, postoperative hematoma, and cutaneous wound dehiscence have a connection in performing postoperative hysterectomies after caesarean births.…”
Section: Introductionmentioning
confidence: 99%